OVERVIEW OF RESEARCH ON THE DEVELOPMENT OF SCHOOL COUNSELING COMPETENCIES FOR GENERAL EDUCATION TEACHERS - LESSONS FOR VIETNAM - Nguyen Thi Phuong Nhung; Pham Xuan Son (Tạp chí Khoa học)
In the context of modern schooling, the role of teachers in supporting students' mental health has become increasingly important. This paper reviews studies on developing school counselling competencies for general education teachers to draw lessons for Vietnam. Through a literature review method, the paper analyzes the essential competency components for counselling work, models, and methods of developing counselling competencies that have been applied in various countries. Based on these findings, the paper recommends designing training programs to enhance teachers' counselling competencies, contributing to building a healthy school environment that supports students' comprehensive psychological development.